On the performance of self-organized TiO2 nanotubes@MnOx as supercapacitor: Influence of the heat treatment, cathodic treatment, water aging, and thermal oxides - Pinto, Thais T.; Núñez-de la Rosa, Yeison; Hammer, Peter [UNESP]; Aquino, José M. (Elsevier, 2022)
The performance of finely dispersed ε-MnO2 over two different self-organized TiO2 nanotubes (Ti/TiO2–NT) substrates used as template, heat-treated in muffle furnace and microwave oven, was assessed as supercapacitor before and after a cathodic treatment (CT) to induce the formation of Ti(III)/oxygen vacancies. The pulsed MnO2 electrodeposition also led to the formation of Ti(III); however, the highest values of specific capacitance (∼200 F g–1 at 5 A g–1) were only attained when a CT (–1.6 V vs. Ag/AgCl/KCl 3 mol L–1 during 5 s using 0.5 mol L–1 of Na2SO4 as electrolyte) was applied regardless of the used substrate. X-ray photoelectron spectroscopy combined with the analysis of the time evolution of the electrochemical impedance (EI) showed that the hydroxylated surface, produced after CT by the reaction between adsorbed H2O and the unstable surface oxygen vacancies in the TiO2, led to a decrease of the charge transfer resistance and an increase of the TiO2–NT@MnO2 film conductivity, indirectly measured through the evolution of the ohmic drop during galvanostatic experiments. The Ti/TiO2–NT substrates and the thermally grown TiO2 oxide also exhibited similar EI performances before and after the CT, independently of the thermal treatment method. However, the total impedance of these samples was higher than that found for the composite electrode. This is an indication of the beneficial effect of the pulsed electrodeposition procedure in improving the conductivity of the TiO2–NT substrate used successfully as template to produce nanosized MnO2 without binders.
Keywords: Black TiO2; Hybrid supercapacitor; Microwave treatment; MnO2; Oxygen vacancy